An approach to an optimal T-head jetty: a numerical simulation case in Chamela Bay, Mexico. Issue 3 (3rd July 2018) - García-Chan, Néstor; Pantoja, Diego A.; Filonov, Anatoliy; Vázquez-Mendéz, Miguel E; Gasca-Ortiz, Tzitlali
ABSTRACT: A mathematical optimization problem is analyzed to obtain the most suitable T-head jetty design in an artificial tidal inlet system. In this study, the T-head jetty is considered optimal when two constraints are satisfied, specifically (1) the velocity of the currents and (2) the turbulence generated by the flow, both are minimal. These constraints are assessed in a control region around the inlet. To resolve the mathematical optimization problem, the hydrodynamic model Delft3D was combined with a derivative-free optimization method, the Nelder–Mead method. The effectiveness of this methodology was tested in a series of numerical experiments made at Chamela Bay on the Mexican Pacific Coast, where it is planned the construction of an artificial channel to connect the bay with a coastal lagoon. With this approach, future negative effects might be analyzed and reduced before modifying this pristine bay.